Menuiu Sebuah Teori Green Marketing - Singgih Santoso (Fakultas Bisnis UKDW, 2009)
Erwironmental concerns hove begun to reshqe the lodscape in which global orgonizdions compete. &rccessfulfirms tend to adapt andJl* to the dynamics of their unique erwironments, typicalfu resulting in changes in both organizational philosophy and behovior. In this arlicle, the outhor discusses many theoraieal models in environmental marketing, which integrate etwironmental conce,rns, in developing marketing policies and proctices. IuIary models, such as atstomer attitude towmd green product, eco-orimtdion model, erwiropreneurial mrketing strategl model, envirownentalty-based marlreting strategl model, And strategic green marketing plarming model, needto be empirically tested before it can be used as an established model.Keywods : erwironment, green marketing, etwironmentallybas ed marketing s tr otegt, cttst onter's p erc eption.